2021
DOI: 10.1039/d1ra00807b
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 1T-MoS2quantum dots-interspersed (Bi1−xFex)VO4heterostructures for electron transport and photocatalytic properties

Abstract: The present study reports trigonal phase molybdenum disulfide quantum dots (MoS2/QDs)-decorated (Bi1−xFex)VO4 composite heterostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…For Bi 4f (Figure b), two strong peaks located at around 159.4 and 164.7 eV correspond to Bi 4f 7/2 and Bi 4f 5/2 , with the splitting of 5.3 eV. These two peaks are characteristic peaks of Bi 3+ ion in BiVO 4 crystal. , The V 2p spectra exhibit two strong peaks at around 524.2 and 516.5 eV (Figure c) that are indexed to V 2p 1/2 and V 2p 3/2 , respectively. These signals can be indexed to V 5+ ions in the BiVO 4 crystal. , We also observed that the positions of Bi 3+ and V 5+ in Pt/PtO x /BiVO 4 composites had a slightly shifted toward higher binding energy, indicating the interaction between Pt/PtO x NPs and BiVO 4 . , The deconvolution analysis of the O 1s peak suggests the presence of two distinct oxygen species.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For Bi 4f (Figure b), two strong peaks located at around 159.4 and 164.7 eV correspond to Bi 4f 7/2 and Bi 4f 5/2 , with the splitting of 5.3 eV. These two peaks are characteristic peaks of Bi 3+ ion in BiVO 4 crystal. , The V 2p spectra exhibit two strong peaks at around 524.2 and 516.5 eV (Figure c) that are indexed to V 2p 1/2 and V 2p 3/2 , respectively. These signals can be indexed to V 5+ ions in the BiVO 4 crystal. , We also observed that the positions of Bi 3+ and V 5+ in Pt/PtO x /BiVO 4 composites had a slightly shifted toward higher binding energy, indicating the interaction between Pt/PtO x NPs and BiVO 4 . , The deconvolution analysis of the O 1s peak suggests the presence of two distinct oxygen species.…”
Section: Resultsmentioning
confidence: 92%
“…These two peaks are characteristic peaks of Bi 3+ ion in BiVO 4 crystal. 35,39 The V 2p spectra exhibit two strong peaks at around 524.2 and 516.5 eV (Figure 2c) that are indexed to V 2p 1/2 and V 2p 3/2 , respectively. These signals can be indexed to V 5+ ions in the BiVO 4 crystal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…57,58 MoS 2 enhanced the catalytic activity as it helped to transfer electrons (electron capture) as compared to the control sample. 59 The defects as well as disorders ascribed to the Bi 3+ , act as the trapping center for e − /h + pairs, and effectively hinder the photo-generated charge carriers recombination. 60 Antibacterial activity of undoped and MoS 2 -doped SnO 2 and Bi (1 and 3%)/MoS 2 -doped SnO 2 QDs is encapsulated in the Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Its chemical formula, MX 2 , signifies the presence of transition metal (M) and sulfur element (X). [26][27][28][29][30] It possesses low toxicity, high mobility, the characteristic of the optical, and high stability. In multi-layer structures, it exhibits semiconductor properties with an indirect bandgap.…”
Section: Introductionmentioning
confidence: 99%